2009
DOI: 10.1016/j.exppara.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani lacking the Golgi GDP-Man transporter LPG2 exhibit attenuated virulence in mammalian hosts

Abstract: Surface phosophoglycans such as lipophosphoglycan (LPG) or proteophosphoglycan (PPG) and glycosylinositol phospholipids (GIPLs) modulate essential interactions between Leishmania and mammalian macrophages. Phosphoglycan synthesis depends on the Golgi GDP-mannose transporter encoded by LPG2. LPG2-null (lpg2 − ) L. major cannot establish macrophage infections or induce acute pathology, whereas lpg2 − L. mexicana retain virulence. lpg2 − L. donovani has been reported to survive poorly in cultured macrophages but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 48 publications
1
45
0
2
Order By: Relevance
“…4A). This was not unexpected, since a lack of robust complementation has been frequently observed in transgenic Leishmania (33)(34)(35). Nine weeks after infection, the mice were sacrificed, and footpad tissue was collected for parasite quantification by limiting dilution.…”
Section: Resultsmentioning
confidence: 99%
“…4A). This was not unexpected, since a lack of robust complementation has been frequently observed in transgenic Leishmania (33)(34)(35). Nine weeks after infection, the mice were sacrificed, and footpad tissue was collected for parasite quantification by limiting dilution.…”
Section: Resultsmentioning
confidence: 99%
“…Although we did not examine directly the expression of LPG by WT exosomes, several lines of evidence suggest that LPG expression on exosomes is likely: 1) we found that leishmania exosomes contain a large number of known leishmania surface proteins, both transmembrane and, like LPG, GPIlinked (13); 2) we also found that leishmania exosomes contain LPG2 (13), which is required for cell surface expression of LPG by L. donovani (31); and 3) leishmania exosomes appeared to be predominantly immunosuppressive, a known property of LPG (29,31).…”
Section: Influence Of Exosomes On Acquired Immune Responsesmentioning
confidence: 99%
“…2/2 L. donovani show reduced infection rates both in vitro in macrophages and in vivo in murine models of infection (31), suggesting that surface phosphoglycans are important for virulence. HSP100 2/2 L. donovani also showed reduced virulence in vitro in macrophages, and HSP100 2/2 L. major was avirulent in vivo while showing no reduced viability as axenic culture forms (16,19).…”
Section: Immunomodulation By Leishmania Exosomes Is Influenced By Vesmentioning
confidence: 99%
“…Analysis for mean fluorescence intensity was done using CellQuest Pro software (BD Biosciences, CA). A total of 20,000 events from each sample were acquired to ensure adequate data, and the histograms and images are representative of three independent experiments (32,33).…”
Section: Synthesis Of Ag Nps and Tiomentioning
confidence: 99%